2020
DOI: 10.1088/1361-651x/abb98f
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation of tensile response of notched bulk metallic glass composite specimens

Abstract: In this work, plane strain finite element and atomistic simulations of tensile response of double edge notched bulk metallic glass composite (BMGC) samples are conducted. A special constitutive model is used to represent the response of the bulk metallic glass matrix along with J 2 flow theory of plasticity to characterize the crystalline dendrites in the former, while a CuZr based glass matrix containing single crystal Cu dendrites is modeled in the latter. It is found that the ratio of notc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…However, catastrophic failure at ambient temperature by forming penetrating shear bands limits their applications in structural and functional materials [8][9][10]. Although numerous strategies have been proposed to improve the ductility of MGs, brittle fracture is still a significant problem [11][12][13][14][15][16][17][18]. The energy of MGs is metastable and can be adjusted by external conditions, such as aging and rejuvenation.…”
Section: Introductionmentioning
confidence: 99%
“…However, catastrophic failure at ambient temperature by forming penetrating shear bands limits their applications in structural and functional materials [8][9][10]. Although numerous strategies have been proposed to improve the ductility of MGs, brittle fracture is still a significant problem [11][12][13][14][15][16][17][18]. The energy of MGs is metastable and can be adjusted by external conditions, such as aging and rejuvenation.…”
Section: Introductionmentioning
confidence: 99%
“…The design of specific sample configurations such as the introduction of notches is one of the main processes inducing the high plasticity and the superior strength in the MGs. [16][17][18][19][20] It is suggested that the notch in the MG samples can reduce the stress concentration and enhance the homogenous plasticity. 21 Furthermore, submicron notch MGs have the potential to be used in electronic devices and micro-electromechanical systems.…”
Section: Introductionmentioning
confidence: 99%
“…Stacking hatch covers is used especially in European countries and in our country [3]. During loading and unloading operations, accidents and permanent damages occur due to ignoring limit values and violating the standard rules [4]. As a result of the accident analysis, the need to review international rules and design criteria was emphasized [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Before steel hatch covers became widely used, until about the 1940s, wooden covers were used and covered with tarpaulin to ensure waterproo ng [1,3,4]. In this context, Maritime Transport in the 21st century is the most used transport route, where 80% of World Trade occurs [5].…”
Section: Introductionmentioning
confidence: 99%